3, 11‐Diaminodibenzo[a, j]phenazine: Synthesis, Properties, and Applications to Tröger's Base‐Forming Ladder Polymerization. Issue 14 (8th February 2023) - Izumi, Saika; Inoue, Keiki; Nitta, Yuya; Enjou, Tomoya; Ami, Takahiro; Oka, Kouki; Tohnai, Norimitsu; Minakata, Satoshi; Fukushima, Takanori; Ishiwari, Fumitaka; Takeda, Youhei
Abstract: A new class of diamino‐substituted π‐extended phenazine compound was synthesized, and its photophysical properties were investigated. The U‐shaped diaminophenazine displayed photoluminescence in solution with moderate quantum yield. The diamino aromatic compound was found applicable to the poly‐condensation with formaldehyde to form Tröger's base ladder polymer. The obtained microporous ladder polymer features high CO2 adsorption selectivity against N2, most likely due to the presence of basic nitrogen atoms in the phenazine rings. Abstract : A new aminophenazine functional molecule : It displays efficient photoluminescence and positive luminochromism in organic solvent. Not only useful it is as luminophore, but also does it serve as a building block for Tröger's base regioregular ladder polymer. The ladder polymer nicely shows reversible adsorption/desorption behavior of carbon dioxide molecule.